Penyediaan Tempat Sampah Dalam Mewujudkan Lingkungan Bersih Di Desa Aikmel Utara, Kabupaten Lombok Timur - Lilis wardanigsih (Postgraduate Program, University of Mataram, 2025)
The aim of this service is to provide rubbish bins which must start with a preventative and persuasive approach, namely conducting socialization, counseling and providing examples in the form of making simple tools that can be immediately put into practice, installed and distributed to the community. awareness and behavior so that waste is not thrown away carelessly. To provide an effective example, simple waste disposal sites (organic and inorganic) were created, distributed to the community and placed in the village head's office and several places in the Sidomukti sub-district location. It is hoped that this service activity will really help the community so that they can provide insight and understanding not to throw rubbish anywhere or into rivers. This service activity can provide input and assist the Asahan Regency Government program in creating a clean, neat, beautiful and healthy environment.